Mobile elderly living community (MELCO): The development of the social community model: a case study - Kouta, Christiana; Kaite, Charis P.; Samaras, George (My University, 2013)
Background: Elderly prefer to be in their own homes rather than being in hospital or residential homes. Communication between elderly and community nurses is essential in caring and mutual interaction and modern technologies like MELCO provides the elderly the feeling of independence and safety. Aim: The aim of this paper is to describe the development of the social community model within the objectives of the MELCO project and its application within the community. Methodology: Three axes were taken in consideration: a) ontology, b) ecological theory and c) social network and information systems analyses for the development of the social community model. Four elderly women participated as a case study in piloting the mobile virtual system. The participants also responded to a short closed ended questionnaire. Results: The analysis of the questionnaire and the discussions with the participants showed that elders found the mobile system useful, easy to use and expressed the actual use of this would help them maintain active. Participants concern of social isolation or dependency on others seems to be trounced through the use of the mobile technology. Conclusions: MELCO social community model is a centric network that enables effective management and collaboration of social and health care teams around the elderly in the community. The teams are virtual, dynamic and collaborative.
Keywords: Elderly; Communications; Health professionals; Community nursing